On the Epidemic of Police Killings - Martinot, Steve (Social justice, 2012)
This essay seeks to clarify conceptually the common structure uniting many of the incidents in the recent crescendo of police killings of people of color, going beyond their shared racist framework. In tandem with the "new Jim Crow" that Michelle Alexander describes, these killings pertain to the role of the police as the selection mechanism enforcing a new color line. The author focuses on the killings of Oscar Grant, Alan Blueford, Trayvon Martin, and Troy Davis. When connected by their common threads, these killings reveal aspects of the cultural structure of racialization in the United States. The essay concludes by looking at the politico-legal goal of this epidemic of killings.